PENETAPAN HARGA JUAL DENGAN METODE COST PLUS PRICING PADA WARUNG SEDERHANA 2 JETIS KULON SURABAYA - DIYAH IKAWATI, ABRIYANA (Jurnal Akuntansi AKUNESA, 2017)
Different methods in basic production pricing will often generates the differences in final product’s price. This condition will eventually causes percentage of profit is far from the targeted. This study aims to analyze calculation of production pricing of Warung Sederhana 2, which located in jetis kulon Gg 10 Wonokromo Surabaya, due to the problem that faced by the Warung regarding the existing bookkeeping practice and production pricing are based on intuition of the owner only. Furthermore this study also aims to implement pricing technique based on accounting method on the Warung. Using qualitative method and interview for data collecting method, this study finds that the implementation of accounting-based product costing yields on better and more accurate product price. Keywords: basic price production, the selling price, cost plus pricing, full costing, variable costing